(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The growing prevalence of antibiotic-resistant bacteria necessitates the search for alternative antimicrobial agents. This study explores the antibacterial and antifungal properties of essential oil (EO) derived from Tanacetum argyrophyllum (T. argyrophyllum), a plant traditionally used in Armenian medicine. The EO was extracted via hydro-distillation, and its chemical composition was analyzed using GC-MS, identifying major constituents such as caryophyllene oxide, β-eudesmol, camphor, and terpinen-4-ol. Antimicrobial activity was evaluated against Gram-positive and Gram-negative bacteria, as well as yeast strains, using the disk diffusion method. The EO exhibited notable inhibitory effects, particularly against Escherichia coli K-12, kanamycin-resistant E. coli pARG-25. Treatment with the EO reduced bacterial viability, leading to a 30% decrease in colony-forming units for both E. coli strains, while their specific growth rates declined by approximately 50% and 60%, respectively. Additionally, the EO affected membrane-associated functions, including proton (H⁺) flux and ATPase activity, in both resistant and non-resistant E. coli strains. In the control strain, the EO inhibited total H⁺ flux—especially the DCCD-sensitive component—by 4.5-fold. In the pARG-25 strain, DCCD-sensitive H⁺ flux was reduced by 1.7-fold. Correspondingly, ATPase activity, particularly its DCCD-sensitive fraction, decreased 1.5-fold in both strains. These studies indicate that T. argyrophyllum EO may disrupt bacterial proton transport and ATP synthesis, underscoring its potential as a natural antimicrobial agent, especially against drug-resistant pathogens.